A Highly Efficient CRISPR-Cas9-Mediated Large Genomic Deletion in Bacillus subtilis - So, Younju; Park, Soo-Young; Park, Eun-Hye; Park, Seung-Hwan; Kim, Eui-Joong; Pan, Jae-Gu; Choi, Soo-Keun (Frontiers in Microbiology, 2017)
In B. subtilis, large genomic deletions have been carried out for genome reduction, antibiotic overproduction, and heterologous protein overexpression. In view of the eco-friendliness of B. subtilis, it is critical that engineering preserves its food-grade status and avoids leaving foreign DNA in the genome. Existing methods of generating large genomic deletions leave antibiotic resistance markers or display low mutation efficiency. In this study, we introduced a clustered regularly interspaced short palindromic repeat (CRISPR)-derived genome engineering technique to develop a highly efficient method of generating large genomic deletions in B. subtilis without any trace of foreign DNA. Using our system, we produced 38 kb plipastatin-synthesizing pps operon deletion with 80% efficiency. The significant increase in mutation efficiency was due to plasmids-delivered Streptococcus pyogenes-originated SpCas9, target-specific sgRNA and a donor DNA template, which produces SpCas9/sgRNA endonuclease complex continuously for attacking target chromosome until the mutagenic repair occurs. Our system produced single-gene deletion in spo0A (~100%), point mutation (~68%) and GFP gene insertion (~97%) in sigE and demonstrated its broad applicability for various types of site-directed mutagenesis in B. subtilis.